Macrocyclic α helical peptide therapeutic modality: A perspective of learnings and challenges. Issue 10 (1st June 2018) - Sawyer, Tomi K.; Partridge, Anthony W.; Kaan, Hung Yi Kristal; Juang, Yu-Chi; Lim, Shuhui; Johannes, Charles; Yuen, Tsz Ying; Verma, Chandra; Kannan, Srinivasaraghavan; Aronica, Pietro; Tan, Yaw Sing; Sherborne, Brad; et al.
Graphical abstract: Abstract: Macrocyclic α-helical peptides have emerged as a compelling new therapeutic modality to tackle targets confined to the intracellular compartment. Within the scope of hydrocarbon-stapling there has been significant progress to date, including the first stapled α-helical peptide to enter into clinical trials. The principal design concept of stapled α-helical peptides is to mimic a cognate (protein) ligand relative to binding its target via an α-helical interface. However, it was the proclivity of such stapled α-helical peptides to exhibit cell permeability and proteolytic stability that underscored their promise as unique macrocyclic peptide drugs for intracellular targets. This perspective highlights key learnings as well as challenges in basic research with respect to structure-based design, innovative chemistry, cell permeability and proteolytic stability that are essential to fulfill the promise of stapled α-helical peptide drug development.